Pengaruh Profesionalisme, Fungsi Badan Pengawas Dan Kompetensi Sumber Daya Manusia Terhadap Kualitas Laporan Keuangan Lembaga Perkreditan Desa Se-Kecamatan Tegallalang - Oktavianti, Ni Kadek Devi; Putra, I Putu Deddy Samtika; Satriya, I Wayan Budi (Hita Akuntansi dan Keuangan, 2025)
This study aims to examine the effect of professionalism, supervisory functions, and human resource competence on the quality of financial reports. This research was conducted at the Village Credit Institution (LPD) in Tegallalang District using a questionnaire and involving 108 respondents. The data analysis method used is multiple linear regression analysis with the help of SPSS 24 software. The results show that (1) Professionalism has a significant effect on the quality of financial reports. (2) Supervisory function has a significant effect on the quality of financial reports. (3) Human resource competence has a significant effect on the quality of financial reports.